Giant supratentorial dermoid cyst in an infant: a case report - Borja-Zapata, Boris (2025)
Background: Dermoid cysts are rare, benign cystic lesions. The giant supratentorial variant is an exceptional presentation, both in terms of location and size. Case description: We report the case of a 6-month-old female infant from northeastern Peru who presented with seizures, progressive cranial enlargement since 4 months of age, and a preliminary diagnosis of a cerebral cyst based on computed tomography (CT). She was referred to a national pediatric referral center in Lima, where contrast-enhanced brain CT revealed a large cystic lesion in the right hemisphere with posterior wall enhancement after contrast administration, thinning of the surrounding brain parenchyma, and signs of hydrocephalus. Laboratory tests showed leukocytosis, and pathological examination confirmed a dermoid cyst with a marked inflammatory component, numerous foamy macrophages, entrapped hair follicles, calcifications, and osseous tissue within the fibrous cyst wall. Conclusion: This case of a dermoid cyst in an infant represents an extremely rare presentation, due to its supratentorial location, the size of the lesion, and the patient's young age. Imaging studies play a key role in diagnosis, surgical planning, and follow-up of this condition.